ASYNCHRONOUS EVOLUTION OF PHYSIOLOGY AND MORPHOLOGY IN ANOLIS LIZARDS. (28th February 2013) - Hertz, Paul E.; Arima, Yuzo; Harrison, Alexis; Huey, Raymond B.; Losos, Jonathan B.; Glor, Richard E.
<x xml:space="preserve">Abstract</x> Species‐rich adaptive radiations typically diversify along several distinct ecological axes, each characterized by morphological, physiological, and behavioral adaptations. We test here whether different types of adaptive traits share similar patterns of evolution within a radiation by investigating patterns of evolution of morphological traits associated with microhabitat specialization and of physiological traits associated with thermal biology in Anolis lizards. Previous studies of anoles suggest that close relatives share the same "structural niche" (i.e., use the same types of perches) and are similar in body size and shape, but live in different "climatic niches" (i.e., use habitats with different insolation and temperature profiles). Because morphology is closely tied to structural niche and field active body temperatures are tied to climatic niches in Anolis, we expected phylogenetic analyses to show that morphology is more evolutionarily conservative than thermal physiology. In support of this hypothesis, we find (1) that thermal biology exhibits more divergence among recently diverged Anolis taxa than does morphology; and (2) diversification of thermal biology among all species often follows diversification in morphology. These conclusions are remarkably consistent with predictions made by anole biologists in the 1960s and 1970s.